2007
DOI: 10.1001/jama.298.19.2267
|View full text |Cite
|
Sign up to set email alerts
|

Effect of a Rapid Response Team on Hospital-wide Mortality and Code Rates Outside the ICU in a Children’s Hospital

Abstract: Institute of Medicine concluded that between 44 000 and 98 000 deaths per year occur in hospitals in the United States as a result of errors. Since publication, these data have captured the attention of the nation, 2,3 resulting in aggressive calls for further research, 4,5 regulatory interventions, [6][7][8] third-party payer involvement, 9,10 and health care organization initiatives to improve this situation. One such initiative, promoted by the Institute for Healthcare Improvement known as the 100 000 Lives… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
235
3
1

Year Published

2008
2008
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 325 publications
(240 citation statements)
references
References 42 publications
1
235
3
1
Order By: Relevance
“…First, the sample size was relatively small compared to other published studies, [2][3][4][5][6][7][8][9][10][11] promoting the possibility that either epoch was not representative of pre-RRT and post-RRT parent populations. Another weakness is that QOD was measured using surrogate endpoints.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…First, the sample size was relatively small compared to other published studies, [2][3][4][5][6][7][8][9][10][11] promoting the possibility that either epoch was not representative of pre-RRT and post-RRT parent populations. Another weakness is that QOD was measured using surrogate endpoints.…”
Section: Discussionmentioning
confidence: 99%
“…1 Clinical studies that have focused on whether RRTs improve restorative care outcomes, frequency of cardiac arrest, and critical care utilization have yielded mixed results. [2][3][4][5][6][7][8][9][10][11] One study suggested that RRTs might provide an opportunity to enhance palliative care of hospitalized patients. 11 In this study, RRT personnel ''felt that prior do-not-resuscitate orders would have been appropriate'' in nearly a quarter of cases.…”
mentioning
confidence: 99%
“…In the inpatient setting, rapid response teams (RRTs) or medical emergency teams (METs) have become increasingly common as a mechanism to respond to acute changes in patient clinical stability with variable improvement in patient outcome. [8][9][10][11] These dedicated multidisciplinary teams are typically composed of providers who are not part of the primary team caring for the patient. A clinical triggers program based on abnormal vital signs was introduced at Denver Health Medical Center as a variation of the RRT program that utilized the primary team caring for the patient as the principal respondents to patients with deteriorating conditions.…”
Section: Introductionmentioning
confidence: 99%
“…Rapid response teams can play a critical role in reducing mortality and code rates [12]. Yet research on improving response times of neonatal rapid response teams is limited.…”
Section: Discussionmentioning
confidence: 99%